Review: The Bonds of Freedom. Feminist Theology and Christian Realism - Muers, Rachel (The journal of theological studies, 2003)
The Bonds of Freedom. Feminist Theology and Christian Realism Rebekah L. Miles viii + 206 New York Oxford University Press 2001 £37.50 0 19 514416 3